Blend of neem oil based polyesteramide as magnetic nanofiber mat for efficient cancer therapy - Patel, Pratikshkumar R.; Singam, Amarnath; Dadwal, Arun; Gundloori, Rathna Venkata Naga (Journal of Drug Delivery Science and Technology, 2022)
Stearic acid-coated magnetic nanoparticles (SMN) and FU (5-Fluorouracil) were immobilized in the blends of neem oil-based polyesteramide and fabricated as nanofiber mat (NM) for controlled release of FU under the influence of an external magnetic field for targeted drug delivery to treat cancer efficiently. Analyzed the surface morphology of the fibers using E-SEM, it was observed that the fibers were smooth with the diameter ranging from 250 to 450 nm. TEM studies showed the uniform distribution of SMN in the nanofibers. The physico-chemical properties of NM and raw materials were analyzed using FTIR, TGA, and XRD. The results suggested that the polymers were well blended. In-vitro FU release studies of the NMs recorded a significant difference in the cumulative percentage of FU release from SMN-NMs. The SMN-NMs released 95% of FU in 4 h, whereas, NMs released 83% of FU in 24 h. The cell viability assay for the NM was evaluated in the L929 mouse fibroblast cells, where >75% of cells were viable. The hemolysis assay for the developed SMN-NF showed <5% of hemolysis, which indicated the NMs were safe for application. The anti-cancer activity of FU loaded SMN-NF was analyzed in the MCF-7 cancer cell line, which recorded more than 50% cell death within 24 h. From SQUID analysis, we found that the 10% SMN were superparamagnetic in nature, the magnetization at 30 kOe was observed to be 4.3 emu/g. Based on the in vitro results, we concluded that the developed SMN-NMs are recommended for in vivo studies to understand their efficacy for the targeted drug delivery to treat cancer.
Keywords: 5-Fluorouracil; drug release; electrospinning; Magnetic nanoparticles; nanofibers; Stearic acid